Boettke's Austrian Critique of Mainstream Economics: An Empiricist's Response - Thomas Mayer (University of California, Department of Economics, 1997)
Many of Boettke''s criticisms of formalist economics are justified. However, he defines it so broadly that it becomes practically synonymous with mainstream economics. Yet he blames it for the specific sins of formalist economics more narrowly defined. And since he treats Austrian econornics as the only viable alternative to mainstream economics he incorrectly awards victory to Austrian economics. It has some valuable ideas to contribute to mainstream econornics, but is not a good replacement for it, since it has serious deficiencies.
Keywords: 330